Age‐related skeletal muscle mass loss and physical performance in Taiwan: Implications to diagnostic strategy of sarcopenia in Asia. Issue 4 (3rd March 2013) - Liu, Li‐Kuo; Lee, Wei‐Ju; Liu, Chien‐Liang; Chen, Liang‐Yu; Lin, Ming‐Hsien; Peng, Li‐Ning; Chen, Liang‐Kung
<x xml:space="preserve">Abstract</x> Aim Skeletal muscle loss is a common feature of aging, and is associated with unfavorable outcomes. Although several indexes of skeletal muscle mass measurement have been developed, the most optimal index for sarcopenia diagnosis among Asian populations has remained unclear. The present study aimed to evaluate the relationship between skeletal muscle mass and physical performance among community‐dwelling people in Taiwan. Methods Data of the I‐Lan Longitudinal Aging Study (ILAS) were retrieved for study. Comparisons between demographic profiles, physical performance and skeletal muscle mass (measured by dual‐energy X‐ray absorptiometry) were carried out. Skeletal muscle mass expressed by lean body mass divided by squared height (LBM/ht2), appendicular muscle mass divided by squared height (ASM/ht2) and percent skeletal muscle index (SMI%) were compared between measurements of physical performance. Results Overall, the data of 532 participants (mean age 64.6 ± 9.5 years, male 53.0%) were retrieved for analysis. Age was associated with poorer physical performance, and decreased ASM/ht2 and LBM/ht2, but not SMI%. Skeletal muscle mass (SMI%) was less significantly related to slow walking speed than ASM/ht2 in men. In women, all three muscle indexes showed no significant association between slow walking speed. In contrast, low handgrip strength was strongly associated with decreased skeletal muscle mass (measured by ASM/ht2 and LBM/ht2, but not SMI%) in both men and women. Conclusions Skeletal muscle mass was significantly associated with handgrip strength along with aging, but the association of skeletal muscle mass and walking speed was less significant. In sarcopenia diagnosis among Asian populations, ASM/ht2 should be the most suitable index for skeletal muscle mass measurements, and physical performance should be measured universally beyond measurements of skeletal muscle mass. Geriatr Gerontol Int 2013; 13: 964–971.